Is there a methodical way to answer a question like these without using trial and error.
'The empty cells are filled by adding the two preceding numbers' The first ones are straight forward but then they get a little trickier.e.g.
-15,_,_,_,-27 and -6,_,_,_,3
Very much appreciated for any simplified method.
'The empty cells are filled by adding the two preceding numbers' The first ones are straight forward but then they get a little trickier.e.g.
-15,_,_,_,-27 and -6,_,_,_,3
Very much appreciated for any simplified method.
-
Let's use variables instead of blank spaces: -15, x, y, z, -27. From the problem description ("The empty cells are filled by adding the two preceding numbers") we know that there's a certain kind of relationship between all these numbers. Let's put those relationships in equation form:
(1) y = -15 + x
(2) z = x + y
(3) -27 = z + y
Let's substitute y from (1) into (2):
(1) y = -15 + x
(2) z = x + (-15 + x) ↔ z = 2x - 15
(3) -27 = z + y
Note that both (1) and (2) involve only x on their right hand side. Let's take advantage of that fact. We substitute y from (1) and z from (2) into (3) and then solve (3) for x:
(1) y = -15 + x
(2) z = 2x - 15
(3) -27 = (2x - 15) + (-15 + x) ↔ -27 = 2x - 15 - 15 + x ↔ -27 = 3x - 30 ↔ 3 = 3x ↔ x = 1
If x = 1, then from (1) y = -14 and from (2) z = -13.
So we have arrived at the following sequence:
-15, 1, -14, -13, -27
Let's test this against the conditions we were given:
-14 = -15 + 1 Checks out
-13 = 1 + (-14) Checks out
-27 = -14 + (-13) Checks out
I hope this helps
(1) y = -15 + x
(2) z = x + y
(3) -27 = z + y
Let's substitute y from (1) into (2):
(1) y = -15 + x
(2) z = x + (-15 + x) ↔ z = 2x - 15
(3) -27 = z + y
Note that both (1) and (2) involve only x on their right hand side. Let's take advantage of that fact. We substitute y from (1) and z from (2) into (3) and then solve (3) for x:
(1) y = -15 + x
(2) z = 2x - 15
(3) -27 = (2x - 15) + (-15 + x) ↔ -27 = 2x - 15 - 15 + x ↔ -27 = 3x - 30 ↔ 3 = 3x ↔ x = 1
If x = 1, then from (1) y = -14 and from (2) z = -13.
So we have arrived at the following sequence:
-15, 1, -14, -13, -27
Let's test this against the conditions we were given:
-14 = -15 + 1 Checks out
-13 = 1 + (-14) Checks out
-27 = -14 + (-13) Checks out
I hope this helps
-
Adding 2.25 will work.
-6, -3,75, -1.5, 0.75, 3
-6, -3,75, -1.5, 0.75, 3